Effect of self-efficacy on self-employment intention of undergraduates: a case of arts undergraduates in Sabaragamuwa University of Sri Lanka - H.T.P.L Perera,; H.M.S. Priyanath, (Journal of Social Review and Development, 2022)
The objective of this paper is to examine the impact of self-efficacy on self-employment intention among arts undergraduates of the Sabaragamuwa University of Sri Lanka. This study employs a quantitative method and data were obtained from 159 respondents for a pre-tested structural questionnaire. The data were analyzed employing a multiple regression model with the support of the SPSS. Findings revealed that the magnitude of the students has a positive impact on self-employment intention. Also, the strength and generality of students will positively impact the self-employment intention of the students of the faculty of social sciences & languages. The finding also pointed out that self-efficacy is significantly associated with entrepreneurial intention among undergraduates. These finding further supports an element of social learning theory which states that self-efficacy is able to influence the entrepreneurial intention among students. As a result, the institution can emphasize strategies to increase the degree of self-efficacy among undergraduates to enhance the level of entrepreneurial intention.